The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/brs.0000000000004446
|View full text |Cite
|
Sign up to set email alerts
|

Early Adherence to Prescribed Brace Wear for Adolescent Idiopathic Scoliosis Is Associated With Future Brace Wear

Abstract: Study Design. Retrospective cohort study. Objective. To assess if initial adherence to prescribed brace wear for adolescent idiopathic scoliosis (AIS) predicts future adherence and curve improvement. Summary of Background Data. AIS bracing can be effective if patients adhere to prescribed brace wear. Previous research has associated age, sex, and brace prescription length with future adherence. We hypothesize that a patient's initial adherence to brace wear may be associated with future adherence and outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 32 publications
(69 reference statements)
0
21
0
Order By: Relevance
“…Subjects who wore orthoses >14.4 h/d during the adaptation period exhibited a significantly lower failure rate of 3.3% (defined as Cobb angle progressed to ≥40°), compared with the failure rate of 29.2% in subjects with <14.4 h/d compliance at the 12-month follow-up visit 22 . In addition, there was a significant difference in the surgery rate at orthosis-weaning visit between the compliance groups of >20 and <20 h/d (28% vs. 20.8%) 14 .…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Subjects who wore orthoses >14.4 h/d during the adaptation period exhibited a significantly lower failure rate of 3.3% (defined as Cobb angle progressed to ≥40°), compared with the failure rate of 29.2% in subjects with <14.4 h/d compliance at the 12-month follow-up visit 22 . In addition, there was a significant difference in the surgery rate at orthosis-weaning visit between the compliance groups of >20 and <20 h/d (28% vs. 20.8%) 14 .…”
Section: Resultsmentioning
confidence: 86%
“…Landauer et al found a lower progression rate in the good compliance group than those in the lower compliance group (22.7% vs. 72.2%) 25 . The compliant group of .14.4 h/d (80% of prescribed time) had a lower curve progression rate compared with the incompliant group at the 24month follow-up, although this difference was not statistically significant (39.1% vs. 68.8%) 22 .…”
Section: Curve Control Under Different Compliance Levelsmentioning
confidence: 80%
See 3 more Smart Citations